THE CEREMONIAL IN SECULAR LIFE CONTEXT. URBAN SETTLEMENT OF LATE HORIZON PERIOD: PUEBLO VIEJO - PUCARÁ, LURIN VALLEY - Lizárraga Ibáñez, Manuel (2009)
The ceremonial aspects within secular life not only occur inside cult specialized zones (as platforms or plazas), instead of this, they can occur inside secular areas of domestic use too (inside residences). The investigations in two functionally distinct zones: domestic and ceremonial; undertook in Pueblo ViejoPucará site, which part of the “Lomas de Lurín” Archaeological Field School Project, directed by Dr. Krzysztof Makowski, have identified some ceremonial events inside households. The excavation results showed that ceremonial performances found in both zones not are using an exclusive “ceremonial vessels complex”, and rather, the same vessels complex that depending on the context perform a double function to be utilitarian or ceremonial. In fact, the ceremonial aspects were not representing a separate worlds (sacred/profane opposition: Durkeim [1912] 1993) but, instead, they were considered to be a part of the daily life, where their existence were depended on the obligations and rituals of the same society.